Penerapan Oketani Breast Massage (OBM) pada ibu postpartum dengan pendekatan Evidence Based Nursing Practice (EBNP) - Halimatussakdiah Halimatussakdiah; Kurniati Puji Lestari; Hamidah Hamidah (Politeknik Kesehatan Kemenkes Aceh, 2023)
Background: Oketani Breast Massage (OBM) is one way to reduce lactation problems in postpartum mothers. So far, not much is known about OBM overcoming lactation problems. OBM has no complications in postpartum patients and babies who are breastfedreastfed, but the hospital has not yet performed this procedure. OBM can be performed by nurses, patients, and their family.Objectives: to describe the application of Oketani Breast Massage (OBM) specifically for postpartum mothers after Sectio Caesarea (SC) with ineffective breastfeeding problems at Dr Zainoel Abidin General Hospital Banda Aceh.Methods: the design used in this study was a case study with a cross-sectional approach involving 3 postpartum SC mothers with the same nursing problem, namely ineffective breastfeeding. The instruments used were a Maternity nursing care format and a tool for measuring breast milk volume. OBM is carried out for 3 days with a frequency of 2 times a day with a duration of 15-30 minutes. Collection was carried out on August 29-September 17, 2022 in the Postpartum room at Rumah Saki Umum Daerah (RSUD) dr. Zainoel Abidin Banda Aceh. The Methode of collecting data was by observation, interviews, measuring the amount of milk production, and the baby’s urinary frequency. Data processing is done descriptively, and data presentation is only descriptively.Results: after respondent OBM intervention was carried out for 3 days each respondent's, the breastfeeding problem in postpartum mothers was resolved. The results showed an increase in the amount of milk production, the frequency of breastfeeding was more than 6 times/day, and the frequency of the baby's urination was more than 5 times/daythe. T baby's bowel movements frequency was 1-2 times/day, and the baby slept quietly.Conclusion: this study's results align with previous studies which state that implementing the OBM intervention for postpartum SC mothers can increase and facilitate milk production.